Urinary excretion of morphine and biosynthetic precursors in mice - Grobe, Nadja (National Academy of Sciences, 2010)
It has been firmly established that humans excrete a small but steady amount of the isoquinoline alkaloid morphine in their urine. It is unclear whether it is of dietary or endogenous origin. There is no doubt that a simple isoquinoline alkaloid, tetrahydropapaveroline (THP), is found in human and rodent brain as well as in human urine. This suggests a potential biogenetic relationship between both alkaloids. Unlabeled THP or [1,3,4-D(3)]-THP was injected intraperitoneally into mice and the urine was analyzed. This potential precursor was extensively metabolized (96%). Among the metabolites found was the phenol-coupled product salutaridine, the known morphine precursor in the opium poppy plant. Synthetic [7D]-salutaridinol, the biosynthetic reduction product of salutaridine, injected intraperitoneally into live animals led to the formation of [7D]-thebaine, which was excreted in urine. [N-CD(3)]-thebaine was also administered and yielded [N-CD(3)]-morphine and the congeners [N-CD(3)]-codeine and [N-CD(3)]-oripavine in urine. These results show for the first time that live animals have the biosynthetic capability to convert a normal constituent of rodents, THP, to morphine. Morphine and its precursors are normally not found in tissues or organs, presumably due to metabolic breakdown. Hence, only that portion of the isoquinoline alkaloids excreted in urine unmetabolized can be detected. Analysis of urine by high resolution-mass spectrometry proved to be a powerful method for tracking endogenous morphine and its biosynthetic precursors.